2015
DOI: 10.1097/bot.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Deltoid Ligament Repair Versus Syndesmotic Fixation in Bimalleolar Equivalent Ankle Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 34 publications
1
59
1
3
Order By: Relevance
“…11 Recent evidence suggests that repairing the deltoid complex at the time of lateral malleolus fixation has subjective, functional, and radiographic outcomes that are similar to lateral malleolus fixation with syndesmotic fixation for bimalleolar equivalent ankle fractures. 14 Previous studies have shown that nonoperative management of deltoid injuries in bimalleolar equivalent ankle fractures has satisfactory results without evidence of postoperative instability or loss of medial clear space reduction. 8,17,20 Zeegers and van der Werken evaluated 169 surgically treated lateral malleolus fractures in which 28 (16.6%) had a concurrent deltoid ligament rupture treated without repair.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent evidence suggests that repairing the deltoid complex at the time of lateral malleolus fixation has subjective, functional, and radiographic outcomes that are similar to lateral malleolus fixation with syndesmotic fixation for bimalleolar equivalent ankle fractures. 14 Previous studies have shown that nonoperative management of deltoid injuries in bimalleolar equivalent ankle fractures has satisfactory results without evidence of postoperative instability or loss of medial clear space reduction. 8,17,20 Zeegers and van der Werken evaluated 169 surgically treated lateral malleolus fractures in which 28 (16.6%) had a concurrent deltoid ligament rupture treated without repair.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the recent literature has investigated deltoid ligament repair instead of syndesmotic repair in bimalleolar equivalent ankle fractures and found comparable subjective, functional, and radiographic outcomes at mid-term follow up. 97 However, to prevent potential chronic instability and late arthrosis, the syndesmosis disruption is typically addressed. In the settings of fibular fracture with deltoid disruption, anatomic reduction of the ankle mortise relies on the fibula to hold the talus in proper alignment.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Recientemente, se han publicado varios estudios que reabren el debate sobre la indicación de reparar o no el ligamento (1,2,8) .…”
Section: A Favor De La Reparaciónunclassified
“…En el mismo año, Jones et al publicaron otro estudio retrospectivo en un grupo de pacientes con fracturas de tobillo con lesión del deltoideo en el que comparaban un grupo de pacientes en los que se sintetizaba la sindesmosis con un tornillo transindesmal con otro grupo de pacientes en los que se reparaba el LD con un anclaje (2) . No encontraron diferencias estadísticamente significativas entre los 2 grupos en las puntuaciones de la escala de la American Orthopaedic Foot and Ankle Society (AOFAS) postoperatoria, la escala visual analógica (VAS) y la prueba de funcionalidad de la extremidad inferior.…”
Section: A Favor De La Reparaciónunclassified